Designing a Bilingual Promotional Website for Sumenep Palace Museum as Linked to Social Media - I’tishomah, Badriyyah Eka; Suyono, Achmad; Suharto, Ririn Pratiwi (International Journal of Social Science and Community Service, 2025)
This research addresses the challenge of promoting cultural heritage through digital innovation by developing a bilingual website for the Sumenep Palace Museum, the only surviving royal palace in East Java. Employing Design and Development Research methodology, the study systematically analyzed informational needs, designed an accessible platform, and implemented bilingual content in Indonesian and English. The website features comprehensive information about the museum's collections, history, and services, integrated with social media connectivity. Expert validation from IT and language specialists yielded scores of 96/100 and 80/100 respectively, while field testing with 59 participants from various nationalities produced a 90% satisfaction rate. The results demonstrate that the bilingual website effectively bridges communication gaps with international visitors, particularly during peak periods when guide availability is limited. The research contributes a practical solution to heritage preservation challenges while establishing a replicable framework for cultural institutions seeking to enhance accessibility and global reach through digital promotion strategies.